Observasi Pembelajaran Dengan Menggunakan Model Pembelajaran Di Kelas - Anggi Rahmani Putri; Fahira, Adinda Luzen; Apriyani, Syainahtul; Khasanah, Uswatun (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This research was carried out with the aim of finding out and investigating the influence of the discussion model in the context of classroom learning by directly observing the factory operational processes in the field. Research Approach This study uses a quantitative approach to measure the impact of the discussion model on student learning outcomes. This approach was chosen because it allows for in-depth statistical analysis of data collected during observation and the use of questionnaire instruments. Qualitative data was obtained from learning activity observation sheets and student response questionnaires which were analyzed descriptively. This approach was chosen because it allows for in-depth statistical analysis of the data collected during observations and the use of questionnaire instruments. Design This research adopts an experimental design pre-test post-test control group design Population and Sample The population of this study is class students... at an elementary school... in Bekasi City. The sample consists of one class which is divided into 2 groups from the population: one group as an experimental group which applies the discussion model, and another group as a control group which uses conventional learning methods.